Urbanization in an Underdeveloped City—Nanning, China and its Impact on a Heavy Rainfall Event in July. Issue 4 (7th April 2020) - Xiao, Zhixiang; Wang, Ziqian; Huang, Mingce; Luo, Xiaoli; Liang, Yiling; Lin, Zhenmin
Abstract: A rapid urbanization process is undergoing in China, exerting significant impacts on local weather and climate. However, rare study pays attention to the underdeveloped regions. An underdeveloped city of Nanning, in southwestern China, is experiencing considerable urbanization. The present urban area of Nanning is 2.8 times larger than that in 1980. Using the Weather Research and Forecasting model coupled with an urban canopy model, two experiments with different urban land use are designed to investigate impacts of Nanning urbanization on a rainstorm occurred in July 2009. Results show simulated precipitation can be significantly improved by the experiment with urbanization effects included. Urbanization leads to a warmer and drier surface, which is favored for the formation of near‐surface low pressure and wind convergence over the city. But the warm‐dry air near urban surface cannot lead to deep convective activity, resulting in urban‐enhanced precipitation is dominated by the large‐scale precipitation. Such enhanced large‐scale precipitation has a positive contribution to atmospheric latent heat release, inducing a heating source in middle troposphere over the urban area. Then the cyclonic circulation around Nanning is intensified according to thermal adaption theory. The enhanced cyclonic circulation is beneficial for stronger moisture convergence and warm‐moist southwesterly flow transports into Guangxi from tropical oceans. Vertical motion is amplified by the coastal orographic uplift effect, and wind convergence over the Nanning downstream is also enhanced. Therefore, the convective precipitation dominantly enhances over the coastal and city's downstream regions, which is different from the urban‐increased large‐scale precipitation in the Nanning City area. Key Points: An underdeveloped city in southwestern China, Nanning, is experiencing a considerable urbanization The urbanization of underdeveloped city also shows significant influences on a heavy rainfall event The dominated rainfall types enhanced by Nanning urbanization in urban area, downstream, and coastal regions are different